2018
DOI: 10.1038/s41598-018-21332-x
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent Enhanced Corrosion of Ti6Al4V in the Presence of H2O2 and Albumin

Abstract: There is increasing concern regarding the biological consequences of metal release from implants. However, the mechanisms underpinning implant surface degradation, especially in the absence of wear, are often poorly understood. Here the synergistic effect of albumin and H2O2 on corrosion of Ti6Al4V in physiological saline is studied with electrochemical methods. It is found that albumin induces a time-dependent dissolution of Ti6Al4V in the presence of H2O2 in physiology saline. Potentiostatic polarisation mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 49 publications
3
32
0
5
Order By: Relevance
“…The cytotoxic effects of vanadium are well documented [32,33], so the further relative reduction in cell viability, compared to control and G4 particles, from 10 days was thought to be due to continued release of V during the culture (there was no distinct difference in the amount of titanium ions released from G4 and G5 particles). The delayed release of the V agrees with corrosion studies on Ti-6Al-4 V alloys, which reported time-dependent corrosion [31,34].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The cytotoxic effects of vanadium are well documented [32,33], so the further relative reduction in cell viability, compared to control and G4 particles, from 10 days was thought to be due to continued release of V during the culture (there was no distinct difference in the amount of titanium ions released from G4 and G5 particles). The delayed release of the V agrees with corrosion studies on Ti-6Al-4 V alloys, which reported time-dependent corrosion [31,34].…”
Section: Discussionsupporting
confidence: 85%
“…This layer (1.5-10 nm thickness) is formed due to the high affinity of Ti for oxygen [29]. This in turn could contribute to a certain degree of resistance to corrosion of titanium implants [30,31]. G5 implant particles contain vanadium (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29][30] Enhanced corrosion and metal release in the presence of proteins have been observed after a few hours at the shortest (for stainless steel AISI 316L in phosphate buffered saline, pH 7.4) 12 and can occur after significantly longer times, e.g., after at least 24 h for a titanium-aluminum-vanadium alloy in the presence of hydrogen peroxide, which can form complexes with titanium in the surface oxide. 27,30 Interestingly, the metal release pattern in one of these harsh in-vitro studies combining proteins and hydrogen peroxide 30 was similar to that observed in-vivo in rat tibia tissue. 31 Hence, in certain environments there is a transition from an initially beneficial effect of proteins to a detrimental effect for material degradation (Fig.…”
Section: Protein-metal Binding and Detachmentmentioning
confidence: 99%
“…Therefore, the addition of hydrogen peroxide to the saline solution was used to mimic the enhanced corrosion environment in both cases. It should be noted that in the presence of H 2 O 2 and Cl − , there is an enhanced corrosion attack, causing more damage due to the appearance of the intergranular stress corrosion cracking in austenitic steel under tensile stress [64][65][66].…”
Section: Introductionmentioning
confidence: 99%